Respon Masyarakat Terkait Hoax Covid-19 - Zata Ismah; Lili Surya Pratiwi; Rema Rurianti (An Nadwah, 2021)
Believing in hoaxes is more deadly than the Covid-19 virus. The hoax came fromthe United States (US), India, Spain, China, Indonesia and Brazil. In thedevelopment of this case, public knowledge is needed on the prevention andtransmission of Covid-19, but unfortunately there are still many people who arevery easy to believe in information that cannot be justified, the source and thetruth. This study aims to determine the level of public knowledge regarding theprevention and transmission of Covid-19 and the public response to the Covid-19hoax. This study used a cross sectional approach. With the data collection methodin the form of giving a questionnaire containing a set of questions to therespondents. The number of respondents in this study as many as 700 respondentswith an age range of 14 years and over was conducted in September 2020. Thedata collected in this study is primary data, namely data obtained directly fromrespondents through structured questionnaires. The results showed that themajority of respondents had a knowledge level of 54% of Covid-19 prevention and96% of respondents' knowledge of Covid-19 transmission and 44% of hoaxes.